Studi Eksperimental Pengaruh Variasi Bahan Kering Terhadap Produksi dan Nilai Kalor Biogas Kotoran Sapi - I Putu Awing Wiratmana; I Gusti Ketut Sukadana; I Gusti Ngurah Putu Tenaya (Jurnal Energi Dan Manufaktur, 2012)
Biogas produced from the fermentation of organic matter by anaerobic bacteria. The calorific valuecontained in biogas depends on the concentration of CH4. Tthe production of CH4 in biogas is affected by CNratio on dry matter which is between 25:1 - 30:1. Cow manure has a C-N ratio of 18:1, so it should beadded to other materials, namely rice husk which has a C-N ratio of 65:1. The purpose of this study is toinvestigate the effect of the addition of rice husk to the production and calorific value of manure biogas.Thetest was performed with a batch system with the addition of15%, 18%, 21% and 24% of the total rice husk100% by weight of dry ingredients used. Observed data was a water manometer height change (?h), themass of biogas and gas composition on biogas.The results shows that the addition of 21% rice husk 100%had the highest production of 0.0597 kg and the highest calorific value is 55,017 kJ and 75.034 kJ byeksperimental and theoretical with CH4 compositon was found 80%.